1999
DOI: 10.1104/pp.119.4.1165
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Calmodulin-Regulated Ca2+-ATPase in the Endoplasmic Reticulum1

Abstract: A unique subfamily of calmodulin-dependent Ca 2؉ -ATPases was recently identified in plants. In contrast to the most closely related pumps in animals, plasma membrane-type Ca 2؉ -ATPases, members of this new subfamily are distinguished by a calmodulin-regulated autoinhibitor located at the N-terminal instead of a C-terminal end. In addition, at least some isoforms appear to reside in non-plasma membrane locations. To begin delineating their functions, we investigated the subcellular localization of isoform ACA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
1
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 53 publications
2
95
1
7
Order By: Relevance
“…This plasma membrane location was corroborated by cytological imaging of SCA1p tagged with a GFPp. In contrast to the fluorescent signal from a similarly tagged Ca 2ϩ pump ACA2p, which showed a reticulate-like endomembrane localization (Hong et al, 1999), SCA1-GFPp showed a peripheral pattern of fluorescence, consistent with a plasma membrane location ( Figure 5). This evidence from a GFPptagged pump was important because it provided an isoform-specific analysis coupled to a cytological verification.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This plasma membrane location was corroborated by cytological imaging of SCA1p tagged with a GFPp. In contrast to the fluorescent signal from a similarly tagged Ca 2ϩ pump ACA2p, which showed a reticulate-like endomembrane localization (Hong et al, 1999), SCA1-GFPp showed a peripheral pattern of fluorescence, consistent with a plasma membrane location ( Figure 5). This evidence from a GFPptagged pump was important because it provided an isoform-specific analysis coupled to a cytological verification.…”
Section: Discussionmentioning
confidence: 68%
“…of the cell, however, verified that the fluorescent signal was localized to the cell periphery, consistent with a plasma membrane location ( Figures 5B and 5C). This pattern was distinct from controls that showed non-plasma membrane locations such as a GFPp-tagged ER-localized pump (ACA2-GFPp; Hong et al, 1999) (Figure 5D) or a soluble GFPp ( Figure 5A). …”
Section: Sca1p Is Located At the Plasma Membranementioning
confidence: 94%
See 1 more Smart Citation
“…In addition, it also has many other functions, such as calcium homeostasis (Hong et al ., 1999), oil and protein body formation (Huang, 1996; Herman, 2008), rubber particle formation (Brown et al ., 2017) and auxin regulation (Friml & Jones, 2010; Kriechbaumer et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…46 Thus, Ca 2 þ homeostasis regulated by the inner membrane-localized Ca 2 þ -ATPases may have a vital role in cell death inhibitory activity of AtBI-1. Interestingly, CaM is known to bind directly to Ca 2 þ -ATPases localized at the ER, 50 suggesting a possibility that AtBI-1 may control cellular Ca 2 þ homeostasis mediated through interaction with CaM and Ca 2 þ -ATPase. Consistent with this hypothesis, an ER-resident Ca 2 þ -ATPase from tobacco (NbCA1) has recently been demonstrated to be an important modulator of PCD induced by pathogens and elicitors, with evidence that cellular Ca 2 þ fluxes are involved.…”
Section: Molecular Analysis Of Atbi-1-interacting Factorsmentioning
confidence: 99%